Surveillance of environmental fungi, with focus on Aspergillus, in a Portuguese Central Hospital. - Sabino, Raquel (2014)
Objectives: Because immunocompromised patients are more prone to acquire nosocomial infections caused by fungi isolated from the environment, e.g. Aspergillus, this study aimed to screen the hospital environment for the presence of fungi and to understand their epidemiology in the different hospital wards analyzed. Methods: During one-year period, four seasonal samplings, i.e., air and hard surface, were performed. A total of 101 air samples and 99 surface samples were collected from the Hematology, Oncology, and Intensive Care Unit (ICU) wards of a Portuguese Central Hospital. Aspergillus isolates were plated for growth as single colonies on malt extract agar with chloramphenicol to check the colony purity and observe colonial morphology. The universal fungal primers ITS1 and ITS4 were used to amplify DNA from all Aspergillus isolates, amplimers were sequenced, and isolates identified to the species-complex level. Statistical analyses were done using SPSS v15.0 program for Windows. Results: Aspergillus was the most frequently recovered fungal genus (20.9%), followed by Cladosporium (18.7%), and Penicillium (17.2%). Thirty-five Aspergillus isolates were collected from the wards with hematological patients (bone marrow transplant and hemato-oncology wards), whereas 15 isolates were recovered from ICU. Among Aspergillus isolates from the hospital environment, those belonging to the species-complexes of versicolores (n = 26; 32.5%), nigri (n = 12; 15.0%), flavi (n = 11; 13.7%), and circumdati (n = 6; 7.5%) dominated. Hemato-Oncology was the ward with higher fungal counts, whereas the bone marrow transplant ward, which is protected by HEPA-filtration of the supply air, showed the lowest numbers in all sampling periods. A significant association (p = 0.001) was found between the season and the Aspergillus complexes isolated, with spring and summer having a larger number of different species-complexes detected in the hospital´s air and on the surfaces. Nevertheless, air counts showed that the autumn was the season with the highest proportion of Aspergillus (one third of the total number of fungi detected). This could be due in part to the presence of construction work near these wards. Conclusion: The knowledge of the epidemiology of environmental fungi in each hospital may allow the establishment of preventive or corrective measures to decrease nosocomial fungal infections.